Responsibility of Swimming Pool Managers for First Aid Standards from the Perspective of Mashlahah Mursalah - Putri, Pramestia Andini; Hidayat, Rahmat (LEGAL BRIEF, 2024)
One thing that needs to be considered in public spaces, such as swimming pools, is the availability of first aid, considering that accidents or things related to visitor safety are very important. Therefore, one thing that needs to be considered is how the first aid health services are in swimming pools, so the study aims to see the standards of first aid in swimming pools. The research method used is empirical juridical with data processing from interviews or direct field observations of 4 swimming pools. From this study it was found that only 2 swimming pools met the safety standard requirements because they provided complete health facilities and 2 more did not have complete health facilities, because safety standards in swimming pools are important based on the analysis of mashlahah mursalah